Veloura: AI Driven Beauty (Blueprint) / Muhamad Hazim Luqman Mohd Haidar ... [et al.] - Mohd Haidar, Muhamad Hazim Luqman; Ahmad Rothman, Ariesya Firzana; Madon, Nur Auni Nabilah; Shahrin, Nurfatin Athirah; Aswadi, Puteri Insyiraah; Mohd Razif, Siti Nurnabilah (2025)
The world is moving at a fast pace, leaving people especially travellers struggling to find time for even simple makeup routines while travelling. Carrying a full makeup set can be inconvenient and take up a large and valuable storage space. At NEXËN, we aim to develop an innovative, travel friendly solution which is a compact, all-in-one makeup product that stamps out storage concerns and allows customers to apply makeup effortlessly anytime and anywhere. Our product, Veloura was designed especially for travellers and ensures convenience, efficiency and beauty on-the-go. Not only that, but our product is also designed with sustainability integrating eco-friendly and vegan ingredients to provide ultimate beauty and nourishments for the skin. We aim to sell our products through the company's official online platforms that involve AI integration to maximise customer satisfaction. We aim to occupy the target market of modern, on-the-go individuals who prioritise convenience, sustainability and vast skincare benefits in their products. We specifically aim to cater frequent travelers who need a compact, sleek, space-saving makeup product that allows them to maintain their daily basic makeup routines. Additionally, our product is very ideal for professionals and students with a fast-paced lifestyle as it will fulfill their demand for having very convenient products. Eco conscious customers who find sustainable and vegan products also find value in our product. With a great marketing and business strategy, our company will gain at least 1-3% of the beauty and skincare market share which is one of the most valuable market shares in the world.